A review on occurrence of emerging pollutants in waters of the MENA region - Haddaoui, I.; Mateo-Sagasta, Javier (Springer, 2021)
Little is known about the occurrence of emerging pollutants (EPs) in waters in the Middle East and North Africa (MENA) region despite the extensive use of low-quality water there. Available data dealing with the sources, occurrence and removal of EPs within the MENA region in different categories of water is collected, presented and analyzed in this literature review. According to the collected database, the occurrence and removal efficiency of EPs in the water matrix in the MENA region is available, respectively, for 13 and six countries of the 18 in total; no available data is registered for the rest. Altogether, 290 EPs have been observed in different water matrices across the MENA countries, stemming mainly from industrial effluents, agricultural practices, and discharge or reuse of treated wastewater (TWW). Pharmaceutical compounds figure among the most frequently reported compounds in wastewater, TWW, surface water, and drinking water. Nevertheless, pesticides are the most frequently detected pollutants in groundwater. Worryingly, 57 cases of EPs have been reported in different fresh and drinking waters, exceeding World Health Organization (WHO) and European Commission (EC) thresholds. Overall, pharmaceuticals, organic compounds, and pesticides are the most concerning EP groups. The review revealed the ineffectiveness of treatment processes used in the region to remove EPs. Negative removals of some EPs such as carbamazepine, erythromycin, and sulfamethoxazole were recorded, suggesting their possible accumulation or release during treatment. This underlines the need to set in place and strengthen control measures, treatment procedures, standards, and policies for such pollutants in the region.